KEKUATAN HUKUM YURISDIKSI MAHKAMAH INTERNASIONAL DALAM KEPUTUSAN INTERNATIONAL COURT OF JUSTICE PRELIMINARY DECISION IN UKRAINE v RUSSIA 2022 - Islami, Diajeng Dhea Annisa Aura; Prawira, M. Rizki Yudha (Esensi Hukum, 2023)
Historically, Ukraine's conflict with Russia dates back to 1991 when the Soviet Union collapsed and its member states seceded. In 2021, Ukraine joined NATO. Russia then felt its national security had been threatened. Russian military operations were then interpreted by Ukraine and several countries in the world as a genocide convention. The International Court of Justice then issued the International Court of Justice Preliminary in Ukraine v Russia (2022). The purpose of the research is to comprehensively and deeply examine the legal force of the jurisdiction of the International Court of Justice based on the International of Justice Preliminary decision in Ukraine v Russia (2022). The research method used is a literature study based on reliable sources as a reference for research, such as accredited scientific research journals, research articles with relevant topics, and international law regulations. The result of the research is that the International Court of Justice Preliminary Decision in Ukraine V Russia (2022) has legal force that must be obeyed by the parties involved in the dispute.